Market-Based Dynamic Capability Model with the Role of Government as Mediator for the Sustainability of SME Enterprises South Meruya, West Jakarta - Sonny Indrajaya; Tine Yuliantini; Suprapto; Nia Kusuma Wardhani; Winda Widianty; Sri Hartono; Zikri Muhammad; Muhamad Maizar (Jurnal Pengabdian Masyarakat, 2026)
Purpose: To examine how market-based dynamic capabilities influence SME sustainability in South Meruya, West Jakarta, emphasizing the mediating role of government support. Method: A conceptual model grounded in Resource-Based and Market-Based View theories was tested using questionnaire data from 25 SMEs, analyzed via Structural Equation Modeling (SEM). Practical Applications: Findings inform targeted training programs and policy frameworks that strengthen SMEs' adaptive capacity, export orientation, and responsiveness to sustainability demands through enhanced market-based knowledge and resource integration. Conclusion: Dynamic capabilities are effectively cultivated when SMEs strategically align market-oriented resources, capabilities, and knowledge within volatile, competitive environments, with government support critically mediating these relationships to foster long-term business sustainability.